2022
DOI: 10.3390/rs14112564
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Gross Primary Production (GPP) in China: Variations, Trends, Attributions, and Prediction Inferred from Multiple Datasets and Time Series Modeling

Abstract: The accurate estimation of gross primary production (GPP) is crucial to understanding plant carbon sequestration and grasping the quality of the ecological environment. Nevertheless, due to the inconsistencies of current GPP products, the variations, trends and short-term predictions of GPP have not been sufficiently well studied. In this study, we explore the spatiotemporal variability and trends of GPP and its associated climatic and anthropogenic factors in China from 1982 to 2015, mainly based on the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 75 publications
2
1
0
Order By: Relevance
“…et al showed that GPP increased by 3.9% per decade. The GPP obtained in this experiment increased by 7.82% over the 20-year period, with an average increase of 3.91% per decade [47], which is basically consistent with the experimental results of Bo et al The regions with more significant growth are mainly located in South America, Central Africa, and parts of South Asia. While Zhao et al found that most of the vegetation GPP in the highlands showed a decreasing trend [48], the higher altitude areas in this experiment, such as the Andes in western South America, also showed a decreasing trend in the vegetation GPP; however, the GPP in the plains increased more rapidly, which is hypothesized to be affected by topographic factors.…”
Section: Overall Increasing Trend In Tropical Gppsupporting
confidence: 91%
“…et al showed that GPP increased by 3.9% per decade. The GPP obtained in this experiment increased by 7.82% over the 20-year period, with an average increase of 3.91% per decade [47], which is basically consistent with the experimental results of Bo et al The regions with more significant growth are mainly located in South America, Central Africa, and parts of South Asia. While Zhao et al found that most of the vegetation GPP in the highlands showed a decreasing trend [48], the higher altitude areas in this experiment, such as the Andes in western South America, also showed a decreasing trend in the vegetation GPP; however, the GPP in the plains increased more rapidly, which is hypothesized to be affected by topographic factors.…”
Section: Overall Increasing Trend In Tropical Gppsupporting
confidence: 91%
“…Previous studies also showed a rapid increase in the annual GPP in the areas covered by deciduous forests. For example, the annual GPP of deciduous forests in the Qin Mountains all showed the largest increasing rates (>10 gC/m 2 /yr) [14,43,44]. The increasing rate of the forest GPP in the Greater Khingan Mountains was usually below 5 gC/m 2 /yr, which was consistent with the estimation from the Global Land Surface Satellite (GLASS) GPP product [45].…”
Section: Gppmax Dominates Annual Gpp Trendsupporting
confidence: 81%
“…Even though there were many studies investigating GPP [14], it remains challenging to monitor GPP across different scales [15]. Over the past decades, eddy covariance (EC) technologies have become crucial tools for deriving GPP through direct observations of CO 2 exchange at the canopy-atmosphere interface [16].…”
Section: Introductionmentioning
confidence: 99%